Understanding biological motion through the lens of animate motion processing - Shen, Li; Yang, Xinlin; Jiang, Yi; Wang, Ying (Frontiers in Psychology, 2025)
Biological motion (BM), the movement generated by living entities, transmits signals of life and conveys vital cues for animacy perception. In this review, we synthesize empirical findings from human and non-human animal studies to reveal how BM enjoys a unique position in visual perception as an animate motion and how it elicits animacy perception. Compared to non-biological and inanimate motions, BM engages specialized perceptual processing mechanisms and a dedicated cortical–subcortical network. Local motion cues, especially the foot movements of terrestrial animals, are pivotal in driving such specificity, and emerging evidence supports the existence of an innate, evolutionarily conserved “Life Detector” or “Step Detector” tuned to such information in the human and other vertebrate brains. The direct perception of animacy from BM relies on the processing of low-level kinematic features and mid-level motion features embedded in both intrinsic joint movements and extrinsic body motion. While ecological constraints and implied internal energy sources may serve as generic factors affecting animacy perception from visual motion, how precise BM features (both in intrinsic and extrinsic movements) combine to influence animacy percepts and the neural implementation remain largely unexplored. Addressing these gaps will help establish a framework for understanding BM through the lens of animate motion processing. This approach will offer deeper insights into how the life detection system hardwired in the vertebrate brain distinguishes animate from inanimate motion, further uncovering its broader cognitive and evolutionary implications.